Young women's consumer knowledge on the problems of wearing shoes - Rivera, Suzette V.
Consumer behavior in the Philippines is a field where there is a need to do more research in the light of the abundance of local and imported goods. For sometime now, clothing after food is one of the highest item in many people's budget. Clothing is not complete without shoes. The focus of this study is the problem of wearing shoes by women ages 18 to 25, an age supposedly having the greatest need for shoes because of various motivations. Responses of 77 dormitory students to a questionnaire regarding their knowledge and buying practices confirmed the hypothesis that indeed young consumers really lack the knowledge of buying shoes. Design and styles of shoes are more associated with aesthetic rather than function. Thus, most often, discomforts are experienced. Foot ailments such as hammertoes, claw toes, neuromas to name a few have been experienced. It appeared that there are really factors that determine a good pair of shoes. A good pair of shoes really provides comfort during wear. It does not really matter whether it is synthetic or pure leather. And actually, a pair of shoes may not only cause discomfort but also aches and pains during wear to the extent of causing deformity of feet and posture.